Hydroponic Agriculture as Business in Digital Era - Asti Marlina; Hanif Zaidan Sinaga; Ahmad Fathan Mujadidi Haqqani (LPPM UIKA Bogor, 2022)
Hydroponic is a farming activity without land and does not require large areas of land, this farming activity can also have potential as a business activity. This agriculture business activity can also help and even overcome problems that will arise from economic uncertainty. Apart from the hydroponic agriculture business activities, the quality of the final product will greatly affect the price which will ultimately affect the total income and profits from the harvest in that period. The hydroponic training in Laladon Village, Ciomas District, Bogor City is expected to increase community income by establishing SMEs and can also improve food security for the community. Business activities require good marketing strategy skills, today marketing activities are carried out through digital channels. The ability of a good marketing strategy will reach a wider market so that the potential of these business activities can generate better profits. A good marketing strategy will consider the level of effectiveness and efficiency of all available channels, by choosing digital channels that are effective and efficient and have an impact on the right marketing strategy and produce better market growth. To increase hydroponic sales, you can implement and develop digital strategies, namely by using whatsapp business, Instagram, TikTok, Facebook and Google Adds.